Cooperation in Classification and Data Analysis Proceedings of Two German-Japanese Workshops - Okada, Akinori; Imaizumi, Tadashi; Bock, Hans-Hermann; Gaul, Wolfgang A. (Studies in Classification, Data Analysis, and Knowledge Organization, 2009)
This volume presents theories, models, algorithms, and applications in clustering, classification, and visualization. It also includes applications of clustering, classification, and visualization in various fields such as marketing, recommendation system, biology, sociology, and social survey. The contributions give insight into new models and concepts and show the variety of research in clustering, classification, and visualization.